2020
DOI: 10.1002/cbin.11464
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile and bioinformatics analysis of circular RNA in intestinal mucosal injury and repair after severe burns

Abstract: Circular RNA (circRNA) is a novel noncoding RNA that is mostly found in humans and animals. Although the flux of circRNA research has increased in recent years, its precise function is still unclear. Some studies demonstrate that circRNAs can function as microRNA (miRNA) sponges involved in the regulation of competitive endogenous RNAs networks and play a crucial role in many biological processes. Other studies show that circRNAs play multiple biological roles in gastrointestinal diseases. However, the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…MiR-683 mimics significantly reduced the luciferase activity of the circMaml2 wild-type reporter gene, but not of the mutated circMaml2, verifying that circMaml2 combines with miR-683 ( Figure 5 C). The QRT-PCR results showed that circMaml2 negatively regulates the expression of miR-683 ( Figure 5 D) because circRNAs act as a ceRNA and compete with mRNA for miRNA binding [ 26 , 27 ]. Four bioinformatics tools (miRWalk, TargetSummary, TargetScan, and RNAInter) were used to predict 54 genes that may be biological targets of miR-683 ( Figure 5 E).…”
Section: Resultsmentioning
confidence: 99%
“…MiR-683 mimics significantly reduced the luciferase activity of the circMaml2 wild-type reporter gene, but not of the mutated circMaml2, verifying that circMaml2 combines with miR-683 ( Figure 5 C). The QRT-PCR results showed that circMaml2 negatively regulates the expression of miR-683 ( Figure 5 D) because circRNAs act as a ceRNA and compete with mRNA for miRNA binding [ 26 , 27 ]. Four bioinformatics tools (miRWalk, TargetSummary, TargetScan, and RNAInter) were used to predict 54 genes that may be biological targets of miR-683 ( Figure 5 E).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we screened the circRNA expression profile in the intestinal tissues of mice after severe burns using circRNA microarray data [ 11 ]. Subsequently, we identified a circRNA with the highest down-regulation factor, namely circRMA_Maml2, which originated from the second exon of Maml2 and formed an end-to-end closed circRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can resist digestion by RNase R and can exist stably in the circular form, which makes it a molecular therapeutic target in a variety of diseases [ 9 , 10 ]. In previous studies, several abnormally expressed circRNAs have been found in the intestinal tissues of severely burned mice, of which circRNA_Maml2 (mmu_circRNA_43775, circBase ID: mmu_circ_0015409) was most significantly down-regulated [ 11 ]. circRNA_Maml2, which originates from the messenger RNA (mRNA) trans-splicing of Maml2 and is formed by the second ring of five exons, is located on chromosome 9 (13619989–13 621 675) and is 1686 bp in length.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study by Zhang et al identified 308 significantly dysregulated circRNAs in the intestinal mucosal cell of severely burnt mice. Of the dysregulated circRNAs, 97 circRNAs were identified as upregulated and 211 circRNAs were identified as downregulated [137]. In particular, further analyses of significantly downregulated circRNAs suggested that circRNA_Maml2 can positively regulate FZD7 through sponging miR-93-3p.…”
Section: Intestinal Injurymentioning
confidence: 97%